A Randomized, Double-Blind, Placebo-Controlled Study to Assess the Efficacy and Tolerability of Gabapentin Enacarbil in Subjects with Restless Legs Syndrome - Lee, Daniel O.; Ziman, Ronald B.; Perkins, A. Thomas; Poceta, J. Steven; Walters, Arthur S.; Barrett, Ronald W. (Journal of clinical sleep medicine, 2011)
To evaluate the efficacy and tolerability of gabapentin enacarbil (GEn) 1200 mg or 600 mg compared with placebo in subjects with moderate-to-severe primary restless legs syndrome (RLS). This 12-week, multicenter, double-blind, placebo-controlled study randomized subjects (1:1:1) to GEn 1200 mg, 600 mg, or placebo. Co-primary endpoints: mean change from baseline in International Restless Legs Scale (IRLS) total score and proportion of responders (rated as "very much" or "much" improved) on the investigator-rated Clinical Global Impression-Improvement scale (CGI-I) at Week 12 LOCF for GEn 1200 mg compared with placebo. Secondary endpoints included GEn 600 mg compared with placebo on the IRLS and CGI-I at Week 12 LOCF and subjective measures for sleep. Safety and tolerability assessments included adverse events. 325 subjects were randomized (GEn 1200 mg = 113; 600 mg = 115; placebo = 97). GEn 1200 mg significantly improved mean [SD] IRLS total score at Week 12 LOCF (baseline: 23.2 [5.32]; Week 12: 10.2 [8.03]) compared with placebo (baseline: 23.8 [4.58]; Week 12: 14.0 [7.87]; adjusted mean treatment difference [AMTD]: -3.5; p = 0.0015), and significantly more GEn 1200 mg-treated (77.5%) than placebo-treated (44.8%) subjects were CGI-I responders (p < 0.0001). Similar significant results were observed with GEn 600 mg for IRLS (AMTD: -4.3; p < 0.0001) and CGI-I (72.8% compared with 44.8%; p < 0.0001). GEn also significantly improved sleep outcomes (Post-Sleep Questionnaire, Pittsburgh Sleep Diary and Medical Outcomes Sleep Scale) compared with placebo. The most commonly reported adverse events were somnolence (GEn 1200 mg = 18.0%; 600 mg = 21.7%; placebo = 2.1%) and dizziness (GEn 1200 mg = 24.3%; 600 mg = 10.4%; placebo = 5.2%). Dizziness increased with increased dose and led to discontinuation in 2 subjects (GEn 1200 mg, n = 1; GEn 600 mg, n = 1). Somnolence led to discontinuation in 3 subjects (GEn 600 mg). GEn 1200 mg and 600 mg significantly improve RLS symptoms and sleep disturbance compared with placebo and are generally well tolerated.